1991
DOI: 10.1080/02652039109374013
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the natural occurrence ofFusariummycotoxins in cereals grown in New Zealand in 1986–1989

Abstract: Fusarium mycotoxins, principally trichothecenes, occurred commonly in grain from crops in the North Island of New Zealand, but were much less common and also at the much lower levels in grains from South Island regions. The principal contaminants were trichothecenes of the nivalenol (NIV) and deoxynivalenol (DON) types. Trichothecenes derived from scirpentriol and T-2 tetraol were not common. Moniliformin occurred very rarely, while zearalenone contamination was not uncommon, but the levels were generally low.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…It is notorious that countries with hot climate have not been presented problems concerned to contamination by ZEA with maize. However, countries with cold and temperate climates have presented high levels and high percentages of contamination by this toxin in maize (13,19,25,28,32,39).…”
Section: Resultsmentioning
confidence: 99%
“…It is notorious that countries with hot climate have not been presented problems concerned to contamination by ZEA with maize. However, countries with cold and temperate climates have presented high levels and high percentages of contamination by this toxin in maize (13,19,25,28,32,39).…”
Section: Resultsmentioning
confidence: 99%
“…DAS, HT2 and T2 were included due to their high toxicity and also their natural occurrence in foods and feeds (IARC, 1993;Ueno, 1983). Despite the fact that corn is one of the substrates susceptible of this type of contamination (Abbas et al, 1986;Chulze et al, 1989;Kim et al, 1993;Lauren et al, 1991;Luo et al, 1992;Okoye, 1993;Omurtag & Yazicioglu, 2001;Park et al, 1996;Scott, 1997 et al, 1988) and Brazil ranking third in world production of corn, there is little information on the occurrence of trichothecenes in Brazilian corn and its products.…”
Section: Introductionmentioning
confidence: 96%
“…The differing toxicities of the members of this group of toxins, as well their structural similarities, also require that the identity of each toxin be confirmed by a system capable of a great degree of reliability such as mass spectrometry. DON and NIV were chosen for this investigation due to their worldwide occurrence (Abbas, Mirocha, & Tuite, 1986;Lauren, Agnew, Smith, & Sayers, 1991;Oliveira, Soares, & Sawazaki, 2001;Park, Smalley, & Chu, 1996;Prado, Oliveira, Ferreira, Corrêa, & Affonso, 1997;Tanaka et al, 1988;Yamashita et al, 1995). DAS, HT2 and T2 were included due to their high toxicity and also their natural occurrence in foods and feeds (IARC, 1993;Ueno, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4,7 Trichothecenes occur in cereals worldwide 6 and contamination in corn is frequently reported. [8][9][10][11][12][13][14][15] There is little information about corn cultivated in Brazil. Prado et al 16 found DON in about 6% of post-harvested corn samples with levels ranging from 102 to 542 ng g -1 in contaminated samples and 104 ng g -1 T2 in one sample.…”
Section: Introductionmentioning
confidence: 99%